Discharge-pumped soft-x-ray laser in neon-like argon - Rocca, Jorge J., author; Tomasel, F. G., author; Marconi, Mario Carlos, author; Shlyaptsev, Vyacheslav N., author; Chilla, J. L. A., author; Szapiro, B. T., author; Gludice, G., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1995)
Starting with the discovery of x-ray lasers in 1984, laser-created plasmas remained for almost a decade, the only medium in which large amplification of soft-x-ray radiation could be obtained. In this paper the recent first demonstration of large soft-x-ray amplification in a discharge-created plasma column, realized utilizing a fast capillary discharge to collisionally excite the 46.9 nm transition of Ne-like, Ar is reviewed. Results of the parametrization of the Ar IX discharge-pumped amplifier, the study of the dynamics of its plasma column, and the measurement of the time history of the laser pulse are reported. Prospects for laser operation at shorter wavelengths are also discussed.
Keywords: ray lasers; produced plasma; soft-x-radiation; argon; radiation heating; amplifiers; pulsed lasers